Influences of self-induced stress on permeation flux and space-time variation of concentration during diffusion of hydrogen in a palladium alloy - Kandasamy, K. (Elsevier B.V., 1995)
The nature of hydrogen diffusion in a tubular membrane of a Pd81Pt19 alloy is discussed. The effect of self-induced stress on (a) the space-time variation of hydrogen concentration and (b) the diffusion flux in the steady state are presented. The experimental results are explained qualitatively assuming that the concentration profile at steady state is non-linear. The activation energy and the pre-exponential factor of the Arrhenius relation for the diffusion coefficient are estimated for hydrogen diffusion in a Pd81Pt19 alloy membrane containing no hydrogen prior to the diffusion process. Estimated values are in good agreement with published experimental results.